Sodium-rich hard carbon material as well as preparation method and application thereof

By loading sodium-rich functional groups on hard carbon materials to form a stable sodium ion embedded structure, the problems of low efficiency and sodium analysis of hard carbon materials for the first time were solved, efficient sodium ion storage and release were achieved, and the overall performance of the battery was improved.

CN119852353APending Publication Date: 2025-04-18SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411908316.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Hard carbon materials are inefficient in sodium ion batteries for the first time, resulting in serious consumption of initial sodium ions, limiting the actual available capacity of the battery, and having sodium dissipation phenomenon, affecting safety and capacity stability.

Method used

Using sodium-rich hard carbon materials, by loading sodium-rich functional groups, including "A-Na-M" and "Na-A" microstructures on the hard carbon support, the transition metal and non-metal elements are used to form a stable sodium ion intercalation structure, which enhances the intercalation potential of sodium ions and prevents sodium evolution.

Benefits of technology

The first-time Coulomb efficiency, chemical stability and electrochemical properties of the material are significantly improved, the precipitation of sodium metals is avoided, and the cycle stability and capacity retention rate of high-rate charging and discharge are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852353A_ABST
    Figure CN119852353A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion battery negative electrode materials, in particular to a sodium-rich hard carbon material and a preparation method and application thereof. The provided sodium-rich hard carbon material is a hard carbon carrier loaded with a sodium-rich functional group, the sodium-rich functional group comprises an 'A-Na-M' microstructure, A is a non-metallic element, and M is a transition metal element; the transition metal provides an anchor point for sodium ions to prevent the sodium ions from randomly moving under a low-voltage condition, so that the embedding potential of sodium is increased, and the metal sodium is prevented from being separated out; due to the existence of non-metallic elements, the strength of a Na-M bond is enhanced, so that the embedding position of sodium is further stabilized, the problem that sodium ions are converted into metal sodium in a low-voltage platform area to be separated out is effectively avoided, and the first coulombic efficiency, chemical stability and electrochemical performance of the material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of negative electrode materials for sodium ion batteries, and in particular to sodium-rich hard carbon materials and preparation methods and applications thereof. Background Art

[0002] Sodium-ion batteries (SIBs) have become a potential choice for large-scale energy storage applications due to their abundant sodium and low cost. Hard carbon materials have become ideal candidates for negative electrode materials of sodium-ion batteries due to their excellent sodium storage performance, wide source of precursors and low cost. However, the low coulombic efficiency of hard carbon materials during the first charge and discharge process has become a major obstacle to their commercial application.

[0003] In the half-cell, sodium metal acts as the counter electrode, providing sufficient sodium ions, and the low first coulombic efficiency has little effect on the battery cycle. However, in the full cell, due to the limited sodium source, the low first coulombic efficiency leads to severe initial sodium ion consumption, limiting the actual available capacity of the battery. The main reasons for the low first coulombic efficiency include irreversible reactions on the surface and inside of hard carbon materials, such as the formation of solid electrolyte interphase (SEI) film, defect reactions with high surface area, and irreversible adsorption of sodium ions by micropores and functional groups.

[0004] The microstructure of hard carbon materials is usually composed of disordered graphite-like layers, which exhibit dual voltage zone characteristics: one is in the slope zone at a higher voltage (about 1.5V to 0.1V), and the other is in the platform zone at a lower voltage (about 0.1V to 0V). The sodium embedding potential in the low-voltage platform zone is close to the precipitation potential of sodium metal, and sodium metal precipitation is prone to occur under high-rate charge and discharge conditions, causing safety problems and capacity decay. Therefore, it is urgent to modify hard carbon materials to avoid sodium precipitation and improve the first coulombic efficiency of hard carbon materials. Summary of the invention

[0005] The purpose of the present application is to provide a sodium-rich hard carbon material and a preparation method and application thereof, aiming to solve the problems of sodium precipitation and low first coulombic efficiency in the use of hard carbon materials in the prior art.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application discloses a sodium-rich hard carbon material, which is a hard carbon carrier loaded with sodium-rich functional groups, wherein the sodium-rich functional groups include an "A-Na-M" microstructure, wherein A is a non-metallic element and M is a transition metal element.

[0008] In some embodiments, the sodium-rich functional group further includes a "Na-A" microstructure, where A is a non-metallic element.

[0009] In some embodiments, in the "A-Na-M" microstructure, the Na element is connected to the M element via a covalent bond or a metallic bond, and the Na element is connected to the A element via an ionic bond.

[0010] In some embodiments, in the "Na-A" microstructure, the Na element and the A element are connected by ionic bonds.

[0011] In some embodiments, the sodium-rich hard carbon material has a slope region capacity ratio of ≤20%, and a platform region capacity ratio of ≥80%.

[0012] In some embodiments, the sodium-rich functional group is located on the surface of the hard carbon carrier or on the porous structure of the surface; wherein the porous structure includes a microporous structure and a mesoporous structure, the pore size of the microporous structure is 0.5nm to 1.5nm, and the pore size of the mesoporous structure is 2nm to 50nm; the specific surface area of ​​the hard carbon carrier is 2 to 100m 2 / g.

[0013] In some embodiments, when the sodium-rich functional group is a "Na-A" microstructure, the mass ratio of the hard carbon support to the "Na-A" microstructure is 10-50:1, and the mass percentage of the A element is 1-5%.

[0014] In some embodiments, when the sodium-rich functional group is an "A-Na-M" microstructure, the mass ratio of the hard carbon support and the "A-Na-M" microstructure is 10 to 50:1, and the mass percentage of the A element is 1 to 2%, and the mass percentage of the M element is 1 to 2%.

[0015] In some embodiments, when the sodium-rich functional group is a combination of a "Na-A" microstructure and an "A-Na-M" microstructure, the mass ratio of the hard carbon support, the "Na-A" microstructure and the "A-Na-M" microstructure is 10 to 50:2 to 1:1, and the mass percentage of the A element is 1 to 15%, and the mass percentage of the M element is 1 to 10%.

[0016] In some embodiments, the A element includes an O element.

[0017] In some embodiments, the M element includes at least one of Ti, Mn, Fe, Ni, and Y.

[0018] In a second aspect, the present application discloses a method for preparing a sodium-rich hard carbon material, comprising the following steps:

[0019] The hard carbon carrier, the sodium salt and the catalyst are mixed and then melt-reacted to obtain a pre-sodiumized hard carbon material intermediate;

[0020] The pre-sodiumized hard carbon material intermediate and the nano sodium storage material are mixed, and then heated to react to prepare a sodium-rich functional group, thereby obtaining a sodium-rich hard carbon material.

[0021] In some embodiments, the temperature of the melt reaction is 600-800° C., and the time is 1-4 hours.

[0022] In some embodiments, the heating reaction is carried out at a temperature of 600 to 1000° C. and for a time of 1 to 3 hours.

[0023] In some embodiments, the hard carbon carrier is obtained by carbonizing a hard carbon precursor material, wherein the hard carbon precursor material includes any one of phenolic resin carbon, glucose carbide, and biomass porous carbon.

[0024] In some embodiments, the sodium salt includes at least one of sodium chloride, sodium nitrate, sodium carbonate, and sodium hydroxide.

[0025] In some embodiments, the catalyst includes at least one of titanium, iron, nickel, cobalt, copper, and manganese.

[0026] In some embodiments, the nano sodium storage material comprises a transition metal oxide.

[0027] In some embodiments, the mass ratio of the hard carbon support, the sodium salt and the catalyst is 1-1.1:0.5-0.6:0.05-0.06.

[0028] In some embodiments, the mass ratio of the pre-sodiumized hard carbon material intermediate to the nano sodium storage material is 70-90:10-30.

[0029] In a third aspect, the present application discloses a negative electrode material, which includes the above-mentioned sodium-rich hard carbon material or the sodium-rich hard carbon material prepared by the above-mentioned method for preparing the sodium-rich hard carbon material.

[0030] In a fourth aspect, the present application discloses a sodium battery, which includes a positive electrode material, a negative electrode material, and an electrolyte, wherein the negative electrode material is the negative electrode material mentioned above.

[0031] The sodium-rich hard carbon material provided in the first aspect of the present application comprises a hard carbon carrier with a porous structure and a sodium-rich functional group loaded on the hard carbon carrier, wherein the sodium-rich functional group comprises an "A-Na-M" microstructure, wherein A is a non-metallic element and M is a transition metal element; the transition metal provides an "anchor point" for the sodium ions, and the covalent bond or metallic bond formed between the transition metal and the sodium ions acts as a "tether" for the sodium ions, preventing the sodium ions from moving freely under low voltage conditions; the stable presence of the "Na-M element" makes it difficult for the sodium ions to move freely in the low potential region, thereby raising the embedding potential of sodium and avoiding the precipitation of metallic sodium; and the presence of non-metallic elements also enhances the strength of the "Na-M" bond, thereby further stabilizing the embedding position of sodium, and when the sodium ions are embedded in the A-Na-M structure, they will transfer electrons with the surrounding non-metallic elements and transition metals, and these microscopic charge transfers will relatively increase the potential of the sodium ions, thereby effectively avoiding the problem of sodium ions being converted into metallic sodium and precipitating in the low voltage platform region. Compared with traditional hard carbon materials, this structure provides a higher sodium ion embedding potential, effectively inhibits unnecessary sodium metal precipitation reactions, reduces the irreversible consumption of sodium ions during the first charge and discharge process, and significantly improves the material's first coulombic efficiency, chemical stability, and electrochemical performance.

[0032] The second aspect of the present application provides a method for preparing a sodium-rich hard carbon material. In the preparation method, an alkali etching technique is used to melt a carbon-based material and a sodium salt under the action of a catalyst to generate a large number of pore structures and introduce sodium ions; the carbon-based material then reacts with a nano sodium storage material to generate a sodium-rich functional group to obtain a sodium-rich hard carbon material. The preparation method is simple to operate, does not require large-scale instruments and equipment, and is conducive to wide use.

[0033] The third aspect of the present application provides a negative electrode material, which includes the above-mentioned sodium-rich hard carbon material. Since the above-mentioned sodium-rich hard carbon material has excellent chemical stability and electrochemical properties, the first coulombic efficiency of the obtained negative electrode material is significantly improved, and it has a higher sodium insertion potential in the low-voltage platform area, avoiding the precipitation problem of sodium metal and improving the cycle stability during high-rate charge and discharge.

[0034] A fourth aspect of the present application provides a sodium battery, which includes a positive electrode material, a negative electrode material, and an electrolyte, wherein the negative electrode material is the above-mentioned sodium battery negative electrode material; since the above-mentioned sodium battery negative electrode material has a higher first coulombic efficiency and cycle stability, the obtained sodium battery has a higher specific capacity, first coulombic efficiency and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0036] Figure 1 This is the first charge and discharge capacity curve provided in Example 1 of the present application;

[0037] Figure 2 This is the SEM scan provided in Example 1 of the present application;

[0038] Figure 3 This is the EDS surface scan image provided in Example 1 of the present application. DETAILED DESCRIPTION

[0039] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0040] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0041] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0042] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0043] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0044] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.

[0045] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0046] The first aspect of the embodiments of the present application discloses a sodium-rich hard carbon material, which is a hard carbon carrier loaded with sodium-rich functional groups, wherein the sodium-rich functional groups include an "A-Na-M" microstructure, wherein A is a non-metallic element and M is a transition metal element.

[0047] The sodium-rich hard carbon material provided in the first aspect of the embodiment of the present application comprises a hard carbon carrier with a porous structure and a sodium-rich functional group loaded in the hard carbon carrier, wherein the sodium-rich functional group comprises an "A-Na-M" microstructure, wherein A is a non-metallic element and M is a transition metal element; the transition metal provides an "anchor point" for the sodium ions, and the covalent bond or metallic bond formed by the transition metal and the sodium ions acts as a "tether" for the sodium ions, preventing the sodium ions from moving freely under low voltage conditions; the stable presence of the "Na-M element" makes it difficult for the sodium ions to move freely in the low potential region, thereby raising the embedding potential of sodium and avoiding the precipitation of metallic sodium; and the presence of the non-metallic element also enhances the strength of the "Na-M" bond, thereby further stabilizing the embedding position of sodium, and when the sodium ion is embedded in the A-Na-M structure, it will transfer electrons with the surrounding non-metallic elements and transition metals, and these microscopic charge transfers will relatively increase the potential of the sodium ions, thereby effectively avoiding the problem of sodium ions being converted into metallic sodium and precipitating in the low voltage platform area. Compared with traditional hard carbon materials, this structure provides a higher sodium ion embedding potential, effectively inhibits unnecessary sodium metal precipitation reactions, reduces the irreversible consumption of sodium ions during the first charge and discharge process, and significantly improves the material's first coulombic efficiency, chemical stability, and electrochemical performance.

[0048] The sodium-rich hard carbon material includes a hard carbon carrier, which has good conductivity, appropriate porosity, and thermal stability to adapt to the high-temperature reaction of the molten salt method. The surface of the hard carbon carrier is formed with a porous structure, which increases the specific surface area and the number of pores of the material. These pores not only provide more embedding sites for sodium ions, but also reduce the aggregation effect of sodium ions, making them more evenly distributed on the electrode surface, thereby reducing irreversible reactions and losses.

[0049] In some embodiments, the specific surface area of ​​the hard carbon support is 2 to 100 m 2 / In some specific embodiments, the specific surface area of ​​the hard carbon carrier includes but is not limited to 2 m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, 65m 2 / g, 70m 2 / g, 75m 2 / g, 80m2 / g, 85m 2 / g, 90m 2 / g, 95m 2 / g、100m 2 / g.

[0050] Furthermore, in the sodium-rich hard carbon material, the hard carbon carrier is loaded with sodium-rich functional groups. Due to the particularly active nature of sodium ions, sodium metal precipitation is very likely to occur during the reaction process, causing safety problems and capacity attenuation. Therefore, the structure of the sodium-rich functional group is loaded on the surface of the hard carbon carrier. The chemical form of the sodium-rich functional group is usually a chemical group of sodium ions combined with oxygen groups or transition metals, not just a simple accumulation of a large number of sodium ions; the sodium-rich functional group mainly exists in the chemical form of sodium, and through the action of chemical bonds, sodium has a relatively stable existence form in the material. The introduction of sodium-rich functional groups allows sodium ions to be more effectively "stored" in the material during the first charge and discharge, which is equivalent to a large amount of sodium ions having been stored in advance. The sodium in the negative electrode is already in an excess state in the initial state. Although it has been consumed after the first discharge, there are still excess sodium ions that can be released during the charging process, thereby ensuring that the first efficiency is higher than 100%; this design ensures that more sodium ions can participate in the reversible reaction, thereby improving the first coulomb efficiency.

[0051] In some embodiments, the sodium-rich functional groups are located on the surface of the hard carbon carrier or in the porous structure of the surface. The internal structure of the hard carbon material is relatively dense, and it is difficult for sodium ions and reactants to penetrate at high temperatures. Therefore, the sodium-rich functional groups are more formed on the surface of the material and in the surface pores. This distribution is mainly generated and stabilized on the surface of the material through chemical reactions on the surface, which helps sodium ions to be quickly embedded and removed from the surface of the material, effectively improving the surface sodium embedding efficiency of the electrode material, and can significantly improve the first coulombic efficiency, electrochemical performance and cycle stability of the material.

[0052] Among them, the porous structure includes microporous structure and mesoporous structure. The pore size of the microporous structure is 0.5nm~1.5nm, and the pore size of the mesoporous structure is 2nm~50nm. On the surface of the hard carbon carrier, a porous structure with large pore size and small pore size alternatingly distributed is formed, which is more conducive to optimizing the transmission path of sodium ions, improving the charging and discharging efficiency, and reducing the irreversible loss caused by internal diffusion.

[0053] Among them, the sodium-rich functional group includes an "A-Na-M" microstructure, wherein A is a non-metallic element and M is a transition metal element. In some embodiments, in the "A-Na-M" microstructure, the Na element is connected to the M element through a covalent bond or a metallic bond, and the Na element is connected to the A element through an ionic bond; the covalent bond or metallic bond formed by the transition metal and the sodium ion plays the role of a "tether" for the sodium ion, preventing the sodium ion from moving arbitrarily under low voltage conditions; the Na element is connected to the A element through an ionic bond, which is conducive to enhancing the strength of the Na-M bond, thereby further stabilizing the embedded position of the sodium.

[0054] In some embodiments, when the sodium-rich functional group is an "A-Na-M" microstructure, the mass ratio of the hard carbon support to the "A-Na-M" microstructure is 10 to 50:1, and the mass percentage of the A element is 1 to 2%, and the mass percentage of the M element is 1 to 2%. In some specific embodiments, when the sodium-rich functional group is an "A-Na-M" microstructure, the mass ratio of the hard carbon support to the "A-Na-M" microstructure includes but is not limited to 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1. Among them, the mass percentage of the A element includes but is not limited to 1%, 1.5%, 2%; the mass percentage of the M element includes but is not limited to 1%, 1.5%, 2%.

[0055] In some embodiments, the sodium-rich functional group also includes a "Na-A" microstructure, where A is a non-metallic element. In some embodiments, in the "Na-A" microstructure, the Na element is connected to the A element through an ionic bond. The A element can "lock" the sodium ions in the "Na-A" microstructure. The A element forms a strong coordination with sodium, making the electron cloud distribution of the sodium ions more uniform and stable, which means that the sodium ions can more easily maintain an oxidized state in the structure and will not be easily reduced to metallic sodium at low voltage.

[0056] In some embodiments, when the sodium-rich functional group is a "Na-A" microstructure, the mass ratio of the hard carbon support to the "Na-A" microstructure is 10 to 50:1, wherein the mass percentage of the A element is 1 to 5%. In some specific embodiments, when the sodium-rich functional group is a "Na-A" microstructure, the mass ratio of the hard carbon support to the "Na-A" microstructure includes but is not limited to 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1. wherein the mass percentage of the A element includes but is not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%.

[0057] In some embodiments, when the sodium-rich functional group is a combination of a "Na-A" microstructure and an "A-Na-M" microstructure, the mass ratio of the hard carbon support, the "Na-A" microstructure and the "A-Na-M" microstructure is 10 to 50:2 to 1:1, and the mass percentage of the A element is 1 to 15%, and the mass percentage of the M element is 1 to 10%. When the sodium-rich functional group is a combination of a "Na-A" microstructure and an "A-Na-M" microstructure, the mass ratio of the "Na-A" microstructure and the "A-Na-M" microstructure is controlled to balance the storage sites and stability of sodium ions. The "Na-A" microstructure provides a rapid sodium insertion site through an ionic bond, thereby improving the initial capacity and rate performance; the "A-Na-M" microstructure enhances the stability of sodium through a metal bond, raises the embedding potential, avoids sodium precipitation and improves cycle stability. If there is too much "Na-A": the stability of sodium ions decreases, sodium is easily precipitated, and the cycle stability and safety are reduced; if there is too much "A-Na-M": the initial capacity and rate performance decrease, and the release of sodium ions is limited.

[0058] In some embodiments, the A element includes an O element.

[0059] In some embodiments, the M element includes at least one of Ti, Mn, Fe, Ni, and Y. The Na element is connected to the M element through a covalent bond or a metallic bond.

[0060] In some embodiments, the capacity of the slope region of the sodium-rich hard carbon material during the first discharge process is ≤20%, and the capacity of the platform region is ≥80%. In the sodium-rich functional group, sodium ions are mainly adsorbed and stored at the edges and defects of the hard carbon surface, and the number of stored sodium ions is relatively small. Therefore, the capacity of the slope region is controlled to be low; while in the low-voltage platform region, sodium is embedded in the hard carbon and anchored to the internal A element through ionic bonds, forming a large number of sodium storage microstructures, accommodating more sodium ions and increasing the capacity of the platform region.

[0061] The second aspect of the embodiment of the present application discloses a method for preparing a sodium-rich hard carbon material, comprising the following steps:

[0062] S01. The hard carbon support, sodium salt and catalyst are mixed and then melt-reacted to obtain a pre-sodium hard carbon material intermediate;

[0063] S02. Mix the pre-sodiumized hard carbon material intermediate and the nano sodium storage material, and then heat them to react to prepare sodium-rich functional groups to obtain a sodium-rich hard carbon material.

[0064] The second aspect of the present application provides a method for preparing a sodium-rich hard carbon material. In the preparation method, an alkali etching technique is used to melt a carbon-based material and a sodium salt under the action of a catalyst to generate a large number of pore structures and introduce sodium ions; the carbon-based material then reacts with a nano sodium storage material to generate a sodium-rich functional group to obtain a sodium-rich hard carbon material. The preparation method is simple to operate, does not require large-scale instruments and equipment, and is conducive to wide use.

[0065] In step S01, the hard carbon carrier, the sodium salt and the catalyst are mixed and then subjected to a melting reaction to obtain a pre-sodiumized hard carbon material intermediate.

[0066] The hard carbon support mainly provides the basic support structure and sodium storage sites.

[0067] In some embodiments, the hard carbon carrier is obtained by carbonizing a hard carbon precursor material, wherein the hard carbon precursor material includes any one of phenolic resin carbon, glucose carbide, and biomass porous carbon. After carbonization, phenolic resin forms a hard carbon material with stable structure and moderate porosity, which is conducive to the embedding and de-embedding of sodium ions; glucose carbide has a high carbonization rate, which is conducive to the generation of microporous structure and helps to provide abundant sodium storage sites; biomass porous carbon is mainly obtained by carbonizing biomass materials. Such materials provide a large specific surface area, which is conducive to the improvement of the specific capacity of negative electrode materials. The selection of these carbon carriers needs to be determined according to the application requirements of the battery. The porosity and structural differences of different carbon carriers will affect the overall sodium ion storage and release efficiency of the material.

[0068] In some embodiments, a method for preparing a hard carbon carrier includes: providing a hard carbon precursor material, pretreating the hard carbon precursor material to obtain a hard carbon precursor material powder; and carbonizing the hard carbon precursor material powder to obtain a hard carbon carrier.

[0069] In some embodiments, the pretreatment includes sequentially performing a cleaning process, a drying process and a pulverizing process.

[0070] In some embodiments, the step of carbonizing the hard carbon precursor material powder includes: providing an inert gas atmosphere and carbonizing the hard carbon precursor material powder at 1100-1200° C. for 2-3 hours.

[0071] In some embodiments, the sodium salt includes at least one of sodium chloride, sodium nitrate, sodium carbonate, and sodium hydroxide. The sodium salt is provided to react with the hard carbon support through a melting process to form a sodium-rich functional group and a microporous structure.

[0072] In some embodiments, the catalyst includes at least one of titanium, iron, nickel, cobalt, copper, and manganese. The catalyst is a metal catalyst, which acts as a reaction promoter in the molten salt preparation process. On the one hand, the specific mechanism of action includes promoting the reaction of sodium ions embedded in the carbon carrier. The metal catalyst can accelerate the decomposition of sodium salts under high temperature conditions and the embedding process of sodium ions, and improve the formation efficiency of sodium-rich functional groups on the surface and in the pores of the carbon carrier; on the other hand, it is conducive to the formation of a uniform pore structure on the surface of the hard carbon carrier. The metal catalyst can help the hard carbon carrier generate a microporous structure and a mesoporous structure with a uniform pore size. This pore structure provides multi-level embedding sites for sodium ions, thereby optimizing the sodium storage performance. In addition, the uniform distribution of pores helps to reduce the local current density during battery charging and discharging, and improve the cyclic stability of the material.

[0073] In some embodiments, the mass ratio of the hard carbon carrier, the sodium salt and the catalyst is 1-1.1:0.5-0.6:0.05-0.06. In some specific embodiments, the mass ratio of the hard carbon carrier, the sodium salt and the catalyst is 1:0.5:0.05. During the reaction, if the amount of the hard carbon carrier added is too little, the overall specific capacity of the material will decrease; too much will make it difficult for the sodium salt and the catalytic metal to fully react, affecting the formation of sodium-rich functional groups.

[0074] During the reaction, the amount of hard carbon carrier added was 1, and the mass ratio of hard carbon carrier to sodium salt was 1:0.5. If the amount of sodium salt is too little, the introduction of sodium-rich functional groups will be insufficient, resulting in a low initial coulombic efficiency; too much may lead to excessive aggregation of sodium, forming irreversible sodium clusters, affecting the battery cycle life.

[0075] During the reaction, the amount of hard carbon carrier added is 1, and the mass ratio of hard carbon carrier to catalyst is 1:0.05. If the amount of catalyst added is too little, the reaction will be incomplete, and the generated pores and functional groups will be insufficient; if the amount of catalyst added is too much, unnecessary metal impurities may be introduced, affecting the conductivity and stability of the material.

[0076] Further, the hard carbon carrier, sodium salt and catalyst are mixed and treated, and then a melt reaction is carried out. In some embodiments, the temperature of the melt reaction is 600-800°C, and the time is 1-4 hours. The alkali melt etching process mainly introduces a porous structure on the surface of the hard carbon carrier to provide a large number of pores. These pores increase the specific surface area of ​​the material and provide uniform distribution sites for sodium ions. The local electric field effect in the pores comes from the spatial limitation of the pores and the distribution of surface charges. In the narrow space of the pores, the charge distribution of sodium ions is limited, which makes it difficult for sodium ions in the pores to physically aggregate into clusters. This "steric hindrance" makes the sodium ion concentration in the pores relatively dispersed. Such a distribution will produce a "relatively stable" local electric field in the pores, thereby increasing the embedding potential of sodium ions in the pores. At the same time, many oxygen-containing groups will be formed on the inner wall of the pores during high-temperature etching. These groups carry a small amount of negative charge, which in turn induces an electric field effect in the pores. Due to the presence of these negatively charged surface groups, sodium ions are attracted when embedded in the pores, and a weak "pull-up" electric field is generated, which raises the embedding potential of sodium ions to above the sodium precipitation potential.

[0077] In some embodiments, the temperature of the melt reaction includes, but is not limited to, any typical but non-limiting point value or the interval value between any two point values ​​such as 600° C., 650° C., 700° C., 750° C., 800° C., etc. The time of the melt reaction includes, but is not limited to, any typical but non-limiting point value or the interval value between any two point values ​​such as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, etc.

[0078] In step S02, the pre-sodiumized hard carbon material intermediate and the nano sodium storage material are mixed, and then heated to react to prepare sodium-rich functional groups and obtain a sodium-rich hard carbon material.

[0079] In some embodiments, the nano sodium storage material includes transition metal oxides. In some specific embodiments, the nano sodium storage material includes but is not limited to TiO2, CuO, Fe3O4, Co3O4, ZnO. The addition of the nano sodium storage material is mainly to form enough sodium-rich functional groups on the surface of the material.

[0080] In some embodiments, the mass ratio of the pre-sodiumized hard carbon material intermediate to the nano sodium storage material is 70-90:10-30. If the amount of nano sodium storage material added is too much, the overall structure of the material will be too loose, affecting the conductivity and stability; the excess of nano sodium storage material may cause uneven distribution of sodium on the surface of the material, resulting in excessive concentration of sodium ions in local areas, increasing the risk of sodium precipitation. In addition, sodium metal may generate irreversible metal precipitates during the cycle, affecting the battery life. If the amount of nano sodium storage material added is too little: it will lead to insufficient A-Na-M microstructure, and stable sodium-rich functional groups cannot be formed, affecting the material's first coulombic efficiency and the sodium ion embedding potential enhancement effect.

[0081] In some embodiments, the temperature of the heating reaction is 600 to 1000 ° C, and the time is 1 to 3 hours. At the heating reaction temperature, the nano sodium storage material and the pre-sodium carbon material intermediate can fully react to form an ideal O-Na-M microstructure. If the temperature of the heating reaction is too high, the structure of the carbon material may be over-graphitized, reducing the porosity and specific surface area in the material, which in turn affects the sodium storage performance. In addition, excessively high temperatures may cause the volatilization of sodium or the decomposition of metal oxides, reduce the sodium content in the material, and lead to insufficient generation of sodium-rich functional groups. If the temperature of the heating reaction is too low, the reaction between the nano sodium storage material and the pre-sodium carbon carrier is incomplete, the A-Na-M microstructure cannot be formed or the quantity is insufficient, and the embedding potential and material stability of sodium ions cannot be effectively improved. In addition, insufficient reaction temperature may also make it difficult for sodium salts to be embedded in the pores of the carbon carrier, resulting in a decrease in the first coulombic efficiency and sodium storage capacity of the material.

[0082] In some specific embodiments, the temperature of the heating reaction includes, but is not limited to, 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., 950° C., 1000° C., and other typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values. The time of the melting reaction includes, but is not limited to, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, and other typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0083] A third aspect of an embodiment of the present application discloses a negative electrode material, which includes the above-mentioned sodium-rich hard carbon material or a sodium-rich hard carbon material prepared by the above-mentioned method for preparing the sodium-rich hard carbon material.

[0084] A negative electrode material is provided in the third aspect of an embodiment of the present application, and the provided negative electrode material includes the above-mentioned sodium-rich hard carbon material. Since the above-mentioned sodium-rich hard carbon material has excellent chemical stability and electrochemical properties, the first coulombic efficiency of the obtained negative electrode material is significantly improved, and it has a higher sodium insertion potential in the low-voltage platform area, which avoids the precipitation problem of sodium metal and improves the cycle stability during high-rate charge and discharge.

[0085] A fourth aspect of an embodiment of the present application discloses a sodium battery, which includes a positive electrode material, a negative electrode material, and an electrolyte, wherein the negative electrode material is the negative electrode material mentioned above.

[0086] A fourth aspect of an embodiment of the present application provides a sodium battery, comprising a positive electrode material, a negative electrode material, and an electrolyte, wherein the negative electrode material is the above-mentioned negative electrode material; since the above-mentioned negative electrode material has a higher first coulombic efficiency and cycle stability, the obtained sodium battery has a higher specific capacity, first coulombic efficiency and cycle life.

[0087] In some embodiments, the sodium battery includes a sodium ion liquid battery and a solid state sodium battery.

[0088] In some embodiments, the sodium ion liquid battery includes a positive electrode material, a negative electrode material, a diaphragm and an electrolyte, wherein the negative electrode material includes the above-mentioned sodium-rich hard carbon material, the positive electrode material includes but is not limited to metallic sodium, the electrolyte includes but is not limited to at least one of ethylene carbonate, ethyl methyl carbonate, etc.; the diaphragm includes but is not limited to a polypropylene microporous diaphragm.

[0089] In some embodiments, the solid-state sodium battery includes a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material includes the above-mentioned sodium-rich hard carbon material, the positive electrode material includes but is not limited to metallic sodium, and the electrolyte is a mixture of a polymer and a Na ion salt, wherein the polymer includes but is not limited to polyethylene oxide, polyacrylonitrile, etc.

[0090] The following describes the invention in conjunction with specific embodiments.

[0091] Example 1

[0092] Preparation of sodium-rich hard carbon materials

[0093] Use phenolic resin as a hard carbon precursor, dissolve the phenolic resin in ethanol, stir evenly and dry to obtain solid powder. Place the powder in a tube furnace, heat to 1100°C under argon atmosphere, and maintain for 2 hours to complete the carbonization process to obtain a hard carbon material;

[0094] The hard carbon material, NaOH and metal catalyst titanium acetate are prepared into a mixed solution in a mass ratio of 1:0.5:0.05, stirred, impregnated and dried at 80°C; then, the mixture is placed in a tube furnace and reacted at 800°C for 2 hours for sufficient alkali melt etching. After cooling to room temperature, it is washed with deionized water several times until the pH value of the washing solution is close to neutral, and then dried to obtain a pre-sodium hard carbon material intermediate;

[0095] The pre-sodiumized hard carbon material intermediate is mixed with TiO2 in a mass ratio of 90:10, placed in a tetrahydrofuran solution and stirred evenly, and then transferred to a rotary evaporator for drying. The dried mixture is heated at 1000°C for 2 hours to obtain a sodium-rich hard carbon material; wherein the sodium-rich hard carbon material includes a sodium-rich functional group, the sodium-rich functional group is an "O-Na-Ti" microstructure, the mass ratio of the hard carbon carrier and the "O-Na-Ti" microstructure is 10:1, and the mass percentage of the O element is 2%, and the mass percentage of the Na element is 3%; please refer to Figure 2 This is the SEM scan of the prepared sodium-rich hard carbon material. Please also refer to Figure 3 It is the element distribution obtained by EDS surface scanning of the prepared sodium-rich hard carbon; it can be observed that the hard carbon surface is covered with sodium-rich functional groups.

[0096] Example 2

[0097] Preparation of sodium-rich hard carbon materials

[0098] Glucose carbide was used as a hard carbon precursor. Glucose carbide was dissolved in ethanol, stirred evenly and dried to obtain a solid powder. The powder was placed in a tube furnace, heated to 1100°C under an argon atmosphere, and maintained for 2 hours to complete the carbonization process and obtain a hard carbon material.

[0099] The hard carbon material, sodium chloride and metal catalyst ferric chloride are prepared into a mixed solution in a mass ratio of 1:1:0.05, stirred, impregnated and dried at 80°C; then, the mixture is placed in a tube furnace and reacted at 700°C for 3 hours for sufficient alkali melt etching. After cooling to room temperature, it is washed with deionized water several times until the pH value of the washing solution is close to neutral, and then dried to obtain a pre-sodium hard carbon material intermediate;

[0100] The pre-sodiumized hard carbon material intermediate is mixed with Fe3O4 in a mass ratio of 95:5, placed in a tetrahydrofuran solution and stirred evenly, and transferred to a rotary evaporator for drying. The dried mixture is heated at 900°C for 3 hours to obtain a sodium-rich hard carbon material; wherein the sodium-rich hard carbon material includes a sodium-rich functional group, the sodium-rich functional group is a combination of an "O-Na-Fe" microstructure and an "O-Na" microstructure, the mass ratio of the hard carbon carrier, the "O-Na-Fe" microstructure and the "O-Na" microstructure is 50:1:1, and the mass percentage of the O element is 5%, and the mass percentage of the Fe element is 2.5%.

[0101] Example 3

[0102] Preparation of sodium-rich hard carbon materials

[0103] Use biomass porous carbon as a hard carbon precursor, dissolve the biomass porous carbon in ethanol, stir evenly and dry to obtain solid powder. Place the powder in a tube furnace, heat to 1100°C under argon atmosphere, and maintain for 2 hours to complete the carbonization process to obtain a hard carbon material;

[0104] The hard carbon material, sodium nitrate and metal catalyst copper chloride are prepared into a mixed solution in a mass ratio of 1:0.5:0.05, stirred, impregnated and dried at 80°C; then, the mixture is placed in a tube furnace and reacted at 600°C for 3 hours for sufficient alkaline melt etching. After cooling to room temperature, it is washed with deionized water several times until the pH value of the washing solution is close to neutral, and then dried to obtain a pre-sodium hard carbon material intermediate;

[0105] The pre-sodiumized hard carbon material intermediate is mixed with CuO in a mass ratio of 97:30, placed in a tetrahydrofuran solution and stirred evenly, and then transferred to a rotary evaporator for drying. The dried mixture is heated at 800°C for 4 hours to obtain a sodium-rich hard carbon material; wherein the sodium-rich hard carbon material includes a sodium-rich functional group, the sodium-rich functional group is an "O-Na-Cu" microstructure, the mass ratio of the hard carbon carrier and the "O-Na-Cu" microstructure is 50:1, and the mass percentage of the O element is 1%, and the mass percentage of the Cu element is 2%.

[0106] Example 4

[0107] Preparation of sodium-rich hard carbon materials

[0108] Use biomass porous carbon as a hard carbon precursor, dissolve the biomass porous carbon in ethanol, stir evenly and dry to obtain solid powder. Place the powder in a tube furnace, heat to 1100°C under argon atmosphere, and maintain for 2 hours to complete the carbonization process to obtain a hard carbon material;

[0109] The hard carbon material, sodium nitrate and metal catalyst cobalt chloride are prepared into a mixed solution in a mass ratio of 1:0.5:0.05, stirred, impregnated and dried at 80°C; then, the mixture is placed in a tube furnace and reacted at 600°C for 3 hours for sufficient alkaline melt etching. After cooling to room temperature, it is washed with deionized water several times until the pH value of the washing solution is close to neutral, and then dried to obtain a pre-sodium hard carbon material intermediate;

[0110] The pre-sodiumized hard carbon material intermediate is mixed with Co3O4 in a mass ratio of 85:15, placed in a tetrahydrofuran solution and stirred evenly, and transferred to a rotary evaporator for drying. The dried mixture is heated at 800°C for 4 hours to obtain a sodium-rich hard carbon material; wherein the sodium-rich hard carbon material includes a sodium-rich functional group, the sodium-rich functional group is a combination of an "O-Na-Co" microstructure and an "O-Na" microstructure, the mass ratio of the hard carbon carrier, the "O-Na-Co" microstructure and the "O-Na" microstructure is 10:1:1, and the mass percentage of the O element is 5%, and the mass percentage of the Co element is 5%.

[0111] Example 5

[0112] Preparation of sodium-rich hard carbon materials

[0113] Use biomass porous carbon as a hard carbon precursor, dissolve the biomass porous carbon in ethanol, stir evenly and dry to obtain solid powder. Place the powder in a tube furnace, heat to 1100°C under argon atmosphere, and maintain for 2 hours to complete the carbonization process to obtain a hard carbon material;

[0114] The hard carbon material, sodium nitrate and metal catalyst manganese chloride are prepared into a mixed solution in a mass ratio of 1:0.5:0.05, stirred, impregnated and dried at 80°C; then, the mixture is placed in a tube furnace and reacted at 600°C for 3 hours for sufficient alkaline melt etching. After cooling to room temperature, it is washed with deionized water several times until the pH value of the washing solution is close to neutral, and then dried to obtain a pre-sodium hard carbon material intermediate;

[0115] The pre-sodiumized hard carbon material intermediate is mixed with MnO in a mass ratio of 70:30, placed in a tetrahydrofuran solution and stirred evenly, and then transferred to a rotary evaporator for drying. The dried mixture is heated at 800°C for 4 hours to obtain a sodium-rich hard carbon material; wherein the sodium-rich hard carbon material includes a sodium-rich functional group, the sodium-rich functional group is a combination of an "O-Na-Mn" microstructure and an "O-Na" microstructure, the mass ratio of the hard carbon carrier, the "O-Na-Mn" microstructure and the "O-Na" microstructure is 10:2:1, and the mass percentage of the O element is 15%, and the mass percentage of the Mn element is 10%.

[0116] Comparative Example 1

[0117] Commercial hard carbon material: Kuraray hard carbon Type 2

[0118] Comparative Example 2

[0119] Preparation of porous hard carbon materials

[0120] Use phenolic resin as a hard carbon precursor, dissolve the phenolic resin in ethanol, stir evenly and dry to obtain solid powder. Place the powder in a tube furnace, heat to 1100°C under argon atmosphere, and maintain for 2 hours to complete the carbonization process to obtain a hard carbon material;

[0121] The hard carbon material, NaOH and metal catalyst titanium acetate were prepared into a mixed solution in a mass ratio of 1:0.5:0.05, stirred, impregnated and dried at 80°C; then, the mixture was placed in a tube furnace and reacted at 800°C for 2 hours for sufficient alkali melt etching. After cooling to room temperature, it was washed with deionized water several times until the pH value of the washing solution was close to neutral, and then dried to obtain a porous hard carbon material.

[0122] The negative electrode materials of Examples 1-5 and Comparative Examples 1-2 are respectively used to prepare secondary batteries. The specific method for preparing the secondary batteries comprises the following steps:

[0123] Secondary battery assembly: The negative electrode material is the negative electrode material obtained in the embodiment and the comparative example. The negative electrode material is mixed with a dispersant carboxymethyl cellulose (CMC), a binder SBR (styrene butadiene rubber) and a conductive agent SP (conductive carbon black) in a mass ratio of 95.8:1.2:2:1, and the ball mill is stirred to obtain a negative electrode slurry. The negative electrode slurry is coated on the surface of an aluminum foil and vacuum dried at 110°C overnight to obtain a negative electrode sheet.

[0124] Positive electrode: metallic sodium.

[0125] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and NaPF6 was added to form an electrolyte, and the concentration of NaPF6 was 1 mol / L.

[0126] Diaphragm: Polypropylene microporous membrane.

[0127] Secondary battery assembly: Assemble button-type secondary batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.

[0128] The electrochemical performance test of each secondary battery assembled above and containing the negative electrode material of the embodiment or the comparative example is carried out by the following test method:

[0129] Rate performance test: The button-type secondary batteries assembled in the embodiment and the comparative example were subjected to constant current charge and discharge test at a rate of 0.2C in the voltage range of 0-1.5V, and their first charge and discharge capacities were recorded to calculate the first coulombic efficiency. After three cycles at this rate, the constant current charge and discharge test was performed at a rate of 5C, and the charge and discharge capacities were recorded. The capacity retention rate at the rate of 5C compared with that at 0.2C was calculated.

[0130] Cycle performance test: The button-type secondary batteries assembled in the embodiment and the comparative example were subjected to constant current charge and discharge test at a rate of 1C in the voltage range of 0-1.5V, and their first and 100th charge and discharge capacities were recorded to calculate the 1C 100-cycle cycle capacity retention rate.

[0131] Table 1

[0132]

[0133]

[0134] It can be seen from Table 1 that the first coulombic efficiency of the batteries obtained in Examples 1 to 5 is more than 97%, and the maximum can reach 116%; the reversible capacity of the batteries obtained in Examples 1 to 5 is 387 mAh / g ( Figure 1 As shown), 371mAh / g, 363mAh / g, 389mAh / g, and 403mAh / g, which are significantly higher than traditional commercial hard carbon materials; and, the sodium insertion potential of the batteries obtained in Examples 1 to 5 in the low voltage platform area is as low as 0.05V and as high as 0.25V, while the sodium insertion potential of the batteries obtained in Comparative Examples 1 and 2 is only 0.01V in the low voltage platform area; in terms of cycle retention rate, the cycle retention rate of the batteries obtained in Examples 1 to 5 can reach more than 94%, while the cycle retention rates of the batteries obtained in Comparative Examples 1 and 2 are 85% and 76%, respectively. It can be seen that the embodiments successfully avoid the problem of sodium metal precipitation and improve the cycle stability during high rate charge and discharge.

[0135] In summary, the sodium-rich hard carbon material provided in the embodiment of the present application includes a hard carbon carrier with a porous structure and a sodium-rich functional group loaded in the hard carbon carrier, wherein the sodium-rich functional group includes an "A-Na-M" microstructure, wherein A is a non-metallic element and M is a transition metal element; the transition metal provides an "anchor point" for the sodium ions, and the covalent bond or metallic bond formed by the transition metal and the sodium ions acts as a "tether" for the sodium ions, preventing the sodium ions from moving freely under low voltage conditions; the stable presence of the "Na-M element" makes it difficult for the sodium ions to move freely in the low potential area, thereby raising the embedding potential of sodium and avoiding the precipitation of metallic sodium; and the presence of non-metallic elements also enhances the strength of the "Na-M" bond, thereby further stabilizing the embedding position of sodium. When the sodium ion is embedded in the A-Na-M structure, it will transfer electrons with the surrounding non-metallic elements and transition metals. These microscopic charge transfers will relatively increase the potential of the sodium ions, thereby effectively avoiding the problem of sodium ions being converted into metallic sodium and precipitating in the low voltage platform area. Compared with traditional hard carbon materials, this structure provides a higher sodium ion embedding potential, effectively inhibits unnecessary sodium metal precipitation reactions, reduces the irreversible consumption of sodium ions during the first charge and discharge process, and significantly improves the material's first coulombic efficiency, chemical stability, and electrochemical performance.

[0136] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A sodium-rich hard carbon material, characterized in that: The sodium-rich hard carbon material is a hard carbon carrier loaded with sodium-rich functional groups, wherein the sodium-rich functional groups include an "A-Na-M" microstructure, wherein A is a non-metallic element and M is a transition metal element.

2. The sodium-rich hard carbon material according to claim 1, characterized in that The sodium-rich functional group also includes a "Na-A" microstructure, where A is a non-metallic element; and / or, In the "A-Na-M" microstructure, the Na element is connected to the M element via a covalent bond or a metallic bond, and the Na element is connected to the A element via an ionic bond; and / or, In the "Na-A" microstructure, the Na element and the A element are connected by ionic bonds.

3. The sodium-rich hard carbon material according to claim 1, characterized in that The sodium-rich hard carbon material has a capacity in the slope region of ≤20% and a capacity in the platform region of ≥80% during the first discharge process; and / or The sodium-rich functional group is located on the surface of the hard carbon carrier or the porous structure of the surface; wherein the porous structure includes a microporous structure and a mesoporous structure, the pore size of the microporous structure is 0.5nm to 1.5nm, and the pore size of the mesoporous structure is 2nm to 50nm; the specific surface area of ​​the hard carbon carrier is 2 to 100m 2 / g.

4. The sodium-rich hard carbon material according to claim 2, characterized in that: When the sodium-rich functional group is a "Na-A" microstructure, the mass ratio of the hard carbon support to the "Na-A" microstructure is 10 to 50:1, and the mass percentage of the A element is 1 to 5%; and / or, When the sodium-rich functional group is an "A-Na-M" microstructure, the mass ratio of the hard carbon support to the "A-Na-M" microstructure is 10 to 50:1, and the mass percentage of the A element is 1 to 2%, and the mass percentage of the M element is 1 to 2%; and / or, When the sodium-rich functional group is a combination of a "Na-A" microstructure and an "A-Na-M" microstructure, the mass ratio of the hard carbon carrier, the "Na-A" microstructure and the "A-Na-M" microstructure is 10-50:2-1:1, and the mass percentage of the A element is 1-15%, and the mass percentage of the M element is 1-10%.

5. The sodium-rich hard carbon material according to claim 2, characterized in that: The A element includes an O element; and / or, The M element includes at least one of Ti, Mn, Fe, Ni, and Y.

6. A method for preparing a sodium-rich hard carbon material, characterized in that: The steps include: The hard carbon carrier, the sodium salt and the catalyst are mixed and then melt-reacted to obtain a pre-sodiumized hard carbon material intermediate; The pre-sodiumized hard carbon material intermediate and the nanometer sodium storage material are mixed, and then heated to react to prepare a sodium-rich functional group, thereby obtaining a sodium-rich hard carbon material.

7. The method for preparing a sodium-rich hard carbon material according to claim 6, characterized in that: The temperature of the melting reaction is 600-800° C. and the time is 1-4 hours; and / or, The heating reaction temperature is 600-1000°C and the time is 1-3 hours; and / or, the hard carbon carrier is obtained by carbonizing a hard carbon precursor material, wherein the hard carbon precursor material includes any one of phenolic resin carbon, glucose carbide, and biomass porous carbon; and / or, The sodium salt includes at least one of sodium chloride, sodium nitrate, sodium carbonate and sodium hydroxide; and / or, The catalyst comprises at least one of titanium, iron, nickel, cobalt, copper and manganese; and / or, The nano sodium storage material comprises transition metal oxide.

8. The method for preparing a sodium-rich hard carbon material according to claim 6, characterized in that: The mass ratio of the hard carbon carrier, the sodium salt and the catalyst is 1-1.1:0.5-0.6:0.05-0.06; and / or, The mass ratio of the pre-sodiumized hard carbon material intermediate to the nanometer sodium storage material is 70-90:10-30.

9. A negative electrode material, characterized in that: The negative electrode material comprises the sodium-rich hard carbon material according to any one of claims 1 to 4 or the sodium-rich hard carbon material prepared by the method for preparing the sodium-rich hard carbon material according to any one of claims 5 to 8.

10. A sodium battery, characterized in that: The sodium battery comprises a positive electrode material, a negative electrode material, and an electrolyte, wherein the negative electrode material is the negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method and application of nitrogen-doped carbon-coated sodium-rich sodium cobalt ferricyanide material

    CN114639808A

  • Preparation method of sodium ion battery negative electrode material, negative electrode plate and sodium ion battery

    CN114639815A

  • Hard carbon negative electrode material and preparation method thereof, mixed negative electrode material and secondary battery

    CN115893369A

  • Tin-based oxide nanocrystal modified hard carbon, sodium ion battery and vehicle

    CN116799219A

  • Hard carbon material and preparation method and application thereof

    CN116947009A